Ultra‐thin, high strength, antibiotic‐eluting sutures for prevention of ophthalmic infection - Kunal S. Parikh; Revaz Omiadze; Aditya Josyula; Richard Shi; Nicole M. Anders; Ping He; Youseph Yazdi; Peter J. McDonnell; Laura M. Ensign; Justin Hanes (Wiley, 2021)
Abstract Sutures are applied almost universally at the site of trauma or surgery, making them an ideal platform to modulate the local, postoperative biological response, and improve surgical outcomes. To date, the only globally marketed drug‐eluting sutures are coated with triclosan for antibacterial application in general surgery. Loading drug directly into the suture rather than coating the surface offers the potential to provide drug delivery functionality to microsurgical sutures and achieve sustained drug delivery without increasing suture thickness. However, conventional methods for drug incorporation directly into the suture adversely affect breaking strength. Thus, there are no market offerings for drug‐eluting sutures, drug‐coated, or otherwise, in ophthalmology, where very thin sutures are required. Sutures themselves help facilitate bacterial infection, and antibiotic eye drops are commonly prescribed to prevent infection after ocular surgeries. An antibiotic‐eluting suture may prevent bacterial colonization of sutures and preclude patient compliance issues with eye drops. We report twisting of hundreds of individual drug‐loaded, electrospun nanofibers into a single, ultra‐thin, multifilament suture capable of meeting both size and strength requirements for microsurgical ocular procedures. Nanofiber‐based polycaprolactone sutures demonstrated no loss in strength with loading of 8% levofloxacin, unlike monofilament sutures which lost more than 50% strength. Moreover, nanofiber‐based sutures retained strength with loading of a broad range of drugs, provided antibiotic delivery for 30 days in rat eyes, and prevented ocular infection in a rat model of bacterial keratitis.